2010
DOI: 10.1007/s12528-010-9030-7
|View full text |Cite
|
Sign up to set email alerts
|

Expressions of critical thinking in role-playing simulations: comparisons across roles

Abstract: The development of critical thinking is crucial in professional education to augment the capabilities of pre-professional students. One method for enhancing critical thinking is participation in role-playing simulation-based scenarios where students work together to resolve a potentially real situation. In this study, undergraduate nursing students were divided into small groups (2-3) to role-play a medical emergency (stroke) within a high fidelity simulation environment. The research team utilized a cross-cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 27 publications
(32 reference statements)
1
18
0
Order By: Relevance
“…Learners must thus focus not only on playing a specific role, but also on trying to achieve an outcome consistent with the worldview of that role, usually by working towards objectives that (in character) they have themselves defined, as individuals or in groups. The RISOS scenario is set in a fictitious district in a named developing country: as we sought opportunities for students to engage fully with their online identity and role (Ertmer et al, 2010), locating RISOS in a real country was crucial for the authenticity of cultural contexts, knowledge and implications.…”
Section: Design Decisionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Learners must thus focus not only on playing a specific role, but also on trying to achieve an outcome consistent with the worldview of that role, usually by working towards objectives that (in character) they have themselves defined, as individuals or in groups. The RISOS scenario is set in a fictitious district in a named developing country: as we sought opportunities for students to engage fully with their online identity and role (Ertmer et al, 2010), locating RISOS in a real country was crucial for the authenticity of cultural contexts, knowledge and implications.…”
Section: Design Decisionsmentioning
confidence: 99%
“…The framework's final reflective stage was represented by a comprehensive debriefing. Like Ertmer et al (2010), we believe that a role play's effectiveness as a learning strategy depends as much on a thorough analysis of what happened, and why, as on the actual role play activities. While a debrief had thus always been part of the RISOS design, the DBR feedback collected in 2010 and 2011 showed just how critical the debriefing was to students' understanding of the wider context and the relevance of RISOS to their learning as professionals.…”
Section: Pedagogical Outcomes: the Conversational Framework In Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of simulation with high-fidelity mannequins has shown to be an effective teaching strategy for nursing students [19][20][21][22] .…”
Section: Critical Thinking Interventionsmentioning
confidence: 99%
“…Research by Ertmer and associates [19] allowed 164 nursing students to play different roles in a simulated scenario (family member, patient, primary nurse, or unlicensed personnel), and concluded that despite effective reflections, these students still reported a lack of confidence in their decision-making ability, even commenting on feeling "panicked" and "not knowing what to do" in the situation.…”
Section: Simulationmentioning
confidence: 99%